Design and control of segmented triple three-phase SPM machines for fault tolerant drives - Sala, Giacomo; Gerada, David; Gerada, C.; Tani, A. (2017)
A new multiphase Surface Permanent Magnet (SPM) machine design is investigated in this paper. The machine has a nine-phase winding arranged in three sectors and supplied by three different Voltage Source Inverters (VSI). Stator segmentation between these sectors is analyzed to improve the machine performance and fault tolerant behaviour. A new adaptable control technique is developed for the different segmentation geometries. Finite element simulations are used in order to validate the model and analyse possible layouts. Finally, an optimized design is proposed and the criticalities of the segmentation solution are explained.